2019
DOI: 10.1111/ans.15329
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preoperative percutaneous transhepatic biliary drainage on post‐operative survival in patients with distal cholangiocarcinoma

Abstract: Background: The aim of this study was to investigate the long-term impact of the type of preoperative biliary drainage used for patients undergoing pancreatoduodenectomy for distal cholangiocarcinoma (DCC). Methods: A total of 84 patients with DCC who underwent preoperative biliary drainage between June 2000 and December 2016 were divided into groups for whom percutaneous transhepatic biliary drainage (PTBD) (n = 24) or endoscopic biliary drainage (EBD) (n = 60) was used. Results: The 5-year overall survival i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…PBD for other types of biliary and periampullary malignancies has a negative effect on oncologic outcomes. 5,26 For pancreatic cancers located anatomically near the AoV, the need for a so-called "notouch isolation technique" has been discussed. 27 Recently, as part of minimally invasive treatment for early stage AoV cancer, many endoscopists have undergone endoscopic papillectomy with promising results.…”
Section: Discussionmentioning
confidence: 99%
“…PBD for other types of biliary and periampullary malignancies has a negative effect on oncologic outcomes. 5,26 For pancreatic cancers located anatomically near the AoV, the need for a so-called "notouch isolation technique" has been discussed. 27 Recently, as part of minimally invasive treatment for early stage AoV cancer, many endoscopists have undergone endoscopic papillectomy with promising results.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, nerve fiber density invaded by tumors could be related to unfavorable outcomes of pCCA patients undergoing curative-intent surgery (47). Regarding preoperative evaluation, preoperative biliary drainage is still debated but needed when obstructive symptoms are present for eCCA patients whereas endoscopic biliary drainage seems to be more suitable for dCCA than percutaneous transhepatic biliary drainage which had lower rates of complications for pCCA (48)(49)(50). Moreover, laboratory assessment on peripheral blood revealed that neutrophil count, fibrinogen-to-lymphocyte ratio (FLR), and FLR-neutrophil score could predict the prognosis of patients with resected eCCA (51).…”
Section: Epidemiology and Risk Factors Past And Currentmentioning
confidence: 99%
“…EBD is typically utilized for dCCA, as the transpapillary approach allows for better access to the tumor site. Although somewhat debated, indications for drainage include relief of obstructive jaundice, bilirubin greater than 10 mg/dL and palliative relief in patients who are not surgical candidates [ 28 , 29 , 30 ]. However, a critical complication to consider is severe cholangitis, which can occur secondary to the introduction of bacteria from the gastrointestinal tract after instrumentation of the biliary tree.…”
Section: Presentation and Preoperative Considerationsmentioning
confidence: 99%